1979
DOI: 10.1002/1097-0142(197903)43:3<980::aid-cncr2820430329>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Steroid hormone receptors in human colon cancers

Abstract: Tumors from patients with primary colon cancer were studied for the presence of steroid hormone receptors for estrogen (E2), progesterone (Prog), dihydrotestosterone (DHT) and glucocorticoid. Ten of 33 (30%) tumors contained high affinity E2 receptors. Four were males and six females with positive assays predominantly from the left colon. Twenty-three of these tumors were also assayed for DHT and Prog and six (26%) contained all three receptors. An additional twelve tumors had at least one receptor, so that 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1
2

Year Published

1990
1990
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(25 citation statements)
references
References 20 publications
2
20
1
2
Order By: Relevance
“…It has been shown, at least in mammary carcinomas, to represent an independent prognostic factor [2]. Besides these "typical" sex-hormone-dependent cancers, SSHR have been found in a whole variety of other cancer types, such as hepatocellular carcinomas [21], colon cancer [1] and malignant melanomas [27,9]. Therefore, it is no surprise that the occurence of SHRs has also been described in squamous cell carcinoma cell lines [17].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown, at least in mammary carcinomas, to represent an independent prognostic factor [2]. Besides these "typical" sex-hormone-dependent cancers, SSHR have been found in a whole variety of other cancer types, such as hepatocellular carcinomas [21], colon cancer [1] and malignant melanomas [27,9]. Therefore, it is no surprise that the occurence of SHRs has also been described in squamous cell carcinoma cell lines [17].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous reports have indicated the existence of estrogen and progesterone receptors in colorectal cancers. 10,11 Yakushiji et al reported that estrogen and estrogen receptor in tumor cells is involved in tumor progression and ovarian metastases, which can easily occur in the premenopausal state when ovarian function is very active. 12 In our patient, a rapid increase in tumor size was observed within only 2 months, during which time irregular vaginal bleeding continued.…”
Section: Discussionmentioning
confidence: 99%
“…ER and PR expression have been associated with a more favorable prognosis and increased survival in breast cancer [7][8][9]. In addition, an active estrogen-signaling pathway attenuated p53 apoptotic responses leading to tumor formation [10].…”
Section: Introductionmentioning
confidence: 99%